Hệ thống chế tài xử phạt vi phạm hành chính: Một số vấn đề cần hoàn thiện - Đức, Bùi Xuân (VNU Journal of Science: Social Sciences and Humanities; Vol 15 No 1, 1999)
In this article, author analyzes and estimates the systems of administrative sanction pursuant to the current law; Points out some unreasonable factors in regulation and application of punishment forms such as; warning, financial punishment, supplemental punishment and other administrative measures. The author also promotes some ideals to perfect them.